2014
DOI: 10.1063/1.4889919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-local exchange on core level shifts for gas-phase and adsorbed molecules

Abstract: Articles you may be interested inUnderstanding chemical reactions of CO2 and its isoelectronic molecules with 1-butyl-3-methylimidazolium acetate by changing the nature of the cation: The case of CS2 in 1-butyl-1-methylpyrrolidinium acetate studied by NMR spectroscopy and density functional theory calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Theoretical studies supporting these 213 experimental findings have shown that sites consisting of at least four Pd atoms prefer to bind O2 214 rather than CO, resulting in dissociation of O2 [41]. These reports together with the aforementioned 215 findings of van den Bossche et al [56] support the interpretation that the origin of the additional 216 component at low binding energy in the O1s spectrum is due to adsorbed oxygen. 217…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Theoretical studies supporting these 213 experimental findings have shown that sites consisting of at least four Pd atoms prefer to bind O2 214 rather than CO, resulting in dissociation of O2 [41]. These reports together with the aforementioned 215 findings of van den Bossche et al [56] support the interpretation that the origin of the additional 216 component at low binding energy in the O1s spectrum is due to adsorbed oxygen. 217…”
supporting
confidence: 78%
“…Since CO normally interacts weakly with Au, the similar 176 spectral weight suggests that the surface is composed mainly of Pd. However, CO is also reported to 177 adsorb on PdO(101) at low temperature, with a O 1s contribution from surface oxygen atoms 178 remaining after CO exposure [56]. Such a contribution cannot be resolved from the CO induced 179 contribution in the Pd 3d5/2 spectrum, but may be discerned from the corresponding O 1s spectra as 180 will be discussed below.…”
mentioning
confidence: 90%
“…[5] However, sincem ost of the errors are associated with the change in the atomic coreoccupation and this is similar for differents ites, these errors largely cancelo ut when taking differences and the relative shifts between sites can thus be more reliably calculated. [5a] For am olecule such as the ESCA molecule, with its large range of chemicals hifts, also the shifts are, however,c hallenging to compute.Recently the core-level shifts were calculated for the ESCA molecule by Vand en Bossche et al [6] and the importance of including exact exchange in the DFT functional for accurate results was pointed out. Here, we extend this work by applying [a] F. A. Delesma, Dr.P .C alaminici,D r. A. M. Kçster Programa de Doctorado en NanocienciasyN anotecnología CINVESTAV,…”
mentioning
confidence: 99%
“…Recently the core-level shifts were calculated for the ESCA molecule by Vand en Bossche et al [6] and the importance of including exact exchange in the DFT functional for accurate results was pointed out. Here, we extend this work by applying [a] F. A. Delesma, Dr.P .C alaminici,D r. A. M. Kçster Programa de Doctorado en NanocienciasyN anotecnología CINVESTAV,…”
mentioning
confidence: 99%
“…In what concerns the dissociative adsorption energies, the trends obtained are different from those for molecular adsorption. This was expected to some extent because for the description of molecular adsorption, non‐local exchange and correlation terms have additional importance when compared with the dissociative adsorption, where chemical bonds with covalent or ionic character are formed . In this work, all the functionals predicted a slightly more exergonic dissociative adsorption of O 2 onto Al 50 than onto Al 50 Al ad , with the exception of M06‐L that predicted the opposite, the adsorption onto Al 50 Al ad is 0.46 eV more exergonic in this case.…”
Section: Resultsmentioning
confidence: 69%